Reading Gender: Cases of Social Representation and Curricular Interpretation - Vendramin, Valerija (Acta Paedagogica Vilnensia, 2006)
In this article, I focus on the concept of curriculum and especially hidden curriculum. I see the latter as a "site" where social and cultural contradictions and rigid representations are most likely to be at work. I also touch upon the problem of research in the sphere of education and gender. Finally, l present a section of the mapping of potentially problematic spots in primary education curricula in Slovenia through the concept of hidden curriculum.
Keywords: education system; gender education; social representation; hidden curriculum